Aloe emodin as an agent to enhance the cytotoxic effects of tamoxifen in breast cancer cells / Dayang Zahidah Abang Othman - Abang Othman, Dayang Zahidah (2012)
Tamoxifen is a well-established therapy of choice for breast cancer management. However, there are growing evidences indicate the emergence of tamoxifen resistances in treating the breast cancer. Aloe emodin (l,8-dihydroxy-3-hydroxymethyl-anthraquinone) is a herbal anthraquinone derivative of aloe vera which has been suggested to induce apoptosis in cancer cells by efficiently limiting various tumour cell proliferation as well as restricting cancer growth without affecting the normal cells. Hence, the objectives of this study are to determine the threshold doses of aloe emodin and tamoxifen in the MCF7 breast cancer cells and to clarify the effect of aloe emodin, tamoxifen and combination of both treatments on the MCF7 breast cancer cells as compared to the MCFIOA normal breast cells using the threshold doses. Cell proliferation assay was initially conducted to determine the threshold doses of tamoxifen and aloe emodin on MCF7 cells. The threshold doses for MCFIOA cells have been determined earlier by other co-researcher in different project. There were three main treatments in this study: aloe emodin, tamoxifen or combination of both which were conducted in both MCF7 and MCFIOA cells. The Trypan blue exclusion assay was then conducted in time dependent manner after each treatment for the MCF7 and MCFIOA cells using the determined threshold doses. The viable cells were identified and counted at the end of 18, 24, 36 and 48 hours.